Pengendalian Internal Terhadap Harga Pokok Pesanan Menggunakan Sistem Accurate Accounting V.5 Enterprise (Studi Kasus Pada Pt X) - Rumia Simanullang (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2024)
A company operational cycle produce result information. Information is used to making a decicion especially accounting information so, accounting information system is needed for a company. This research did in PT X which located in Jakarta. Data collection techniques are document analysis, observation, and interview. The Result of the research about cost of goods manufactured with job order costing method in PT X isCost of goods manufactured report obtained from cost of raw materials, direct labour, and factory overhead by using Accurate Accounting V.5 Enterprise system. Internal control substance authorization document and structure organization fungtion already done well. but, PT X still doesn’t implementation the internal control system on cost of goods manufactured well. In substance of employees of appropriate quality of responsibility hasn’t been done because of department production employee and department engineering employee not yet competent in inputting data which causes costof goods manufactured isn’t accurate.